Serum Mac‐2 binding protein levels as a novel diagnostic biomarker for prediction of disease severity and nonalcoholic steatohepatitis. Issue 9 (17th September 2013) - Kamada, Yoshihiro; Fujii, Hideki; Fujii, Hironobu; Sawai, Yoshiyuki; Doi, Yoshinori; Uozumi, Naofumi; Mizutani, Kayo; Akita, Maaya; Sato, Motoya; Kida, Sachiho; Kinoshita, Noriaki; Maruyama, Nobuhiro; et al.
<x xml:space="preserve">Abstract</x> Purpose Mac‐2 binding protein (Mac‐2bp) is one of the major fucosylated glycoproteins, which we identified with glycol‐proteomic analyses. We previously reported that fucosylated glycoproteins are secreted into bile, but scarcely secreted into sera in normal liver and hypothesized that the fucosylation‐based sorting machinery would be disrupted in ballooning hepatocytes due to the loss of cellular polarity. In the present study, we investigated the availability of Mac‐2bp for differential diagnosis of nonalcoholic steatohepatitis (NASH) from nonalcoholic fatty liver disease (NAFLD) as a biomarker. Experimental design Serum Mac‐2bp levels were determined with our developed ELISA kit. Our cohort of 127 patients with NAFLD had liver biopsy to make a histological diagnosis of NASH and simple fatty liver. Results Mac‐2bp levels were significantly elevated in NASH patients compared with non‐NASH (simple steatosis) patients (2.132 ± 1.237 vs. 1.103 ± 0.500 μg/mL, p < 0.01). The area under the receiver‐operating characteristic curve for predicting NASH by Mac‐2bp was 0.816. Moreover, multivariate logistic regression analyses showed Mac‐2bp levels could predict the fibrosis stage and the presence of ballooning hepatocytes in NAFLD patients. Conclusions and clinical relevance These results support the potential usefulness of measuring Mac‐2bp levels in clinical practice as a biomarker for NASH.